Limitations of informed consent in routine clinical practice - An observational survey study to characterize patient populations with limited understanding of the routine informed consent process in an anaesthesia clinic - Elisabeth Bär; Tobias Bock; Bettina Bock; Anne Goldbach; Julia Heusner; Saskia Schuppener; Sven Bercker (BMC Anesthesiology)
Abstract Background Informed consent is a fundamental component of patient autonomy and legal protection. Effective understanding of medical information depends on health literacy, which is influenced by factors such as age, educational level and cognitive ability. This study aims to identify patient groups with limited understanding of the informed consent process for anaesthesia and to assess the factors influencing their understanding. Methods A monocentric, prospective, observational survey study was conducted at the Anaesthesia Clinic of the University Hospital of Leipzig. A total of 501 patients were interviewed using a structured questionnaire, 489 were analysed for demographic data. 12 patients were excluded in the first place due to incomplete data and a further 135 could not be used in the analysis for the comparison groups. Participants were divided into two groups: All patients who answered at least one of the comprehension-related questions incorrectly were assigned to group V0 (limited understanding), while V1 (full understanding) contained all those who were able to answer all questions correctly. Comparisons between groups were conducted via Mann-Whitney U test for ordinal and continuous variables, and the chi-square (χ²) test for nominal variables. Results Patients with limited understanding were generally older, less likely to be employed (including retired patients), and had lower educational attainment. They also had a higher need for physical assistance. A history of psychiatric treatment was more common in those with full understanding. No significant differences were observed regarding non-physical assistance, anaesthetist experience, length of consultation or the proportion of non-German speakers and foreign-born patients. Conclusions Comprehension of medical information is influenced by individual factors and patient health literacy. Targeted communication strategies, such as the use of simplified language and visual aids, are needed to improve patient understanding. Future research should focus on the development and implementation of interventions to improve patient understanding and overall health literacy.